2007
DOI: 10.1089/vbz.2006.0539
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of Epidemiology of Filth Flies: Musca domestica, Musca domestica vicina, Drosophilia melanogaster and Associated Bacteria Pathogens in Ekpoma, Nigeria

Abstract: Between January 2005 and December 2005, including the wet and dry seasons, 1,358 filth flies (Musca domestica, 737 [54.3%]; M. domestica vicina 556 [41%]; and Drosophilia melanogaster 65 [5%]) were caught by quadrant samplings using nets twice each month (early and later) in each of the various sites with varying sanitary conditions in Ekpoma, Nigeria. These sites were markets, hospitals, houses/human habitations, pit latrines, stalls of local food vendors, abattoirs/slaughterhouses, and dairy farms. These fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…For example, inadequate sanitation in the community can cause the release of pathogens into the soil or promote the transport of pathogens through flies. 7 Water runoff, governed by ecological factors such as rain and soil moisture content, may facilitate the spread of these pathogens throughout a community, resulting in contamination of primary water sources. 8,9 Drinking untreated water from these primary sources may result in infection and additional transmission.…”
Section: Introductionmentioning
confidence: 99%
“…For example, inadequate sanitation in the community can cause the release of pathogens into the soil or promote the transport of pathogens through flies. 7 Water runoff, governed by ecological factors such as rain and soil moisture content, may facilitate the spread of these pathogens throughout a community, resulting in contamination of primary water sources. 8,9 Drinking untreated water from these primary sources may result in infection and additional transmission.…”
Section: Introductionmentioning
confidence: 99%
“…(4,5,7), Shigella spp. (4,5,(8)(9)(10), Vibrio cholerae (4,9), Escherichia coli, including enterohemorrhagic E. coli (4,5,7,8,(11)(12)(13), Bacillus cereus (8), Cryptosporidium spp. (3,(14)(15)(16), Giardia lamblia (3), and rotavirus (17).…”
mentioning
confidence: 99%
“…Some non-biting flying insects, particularly the common housefly (Musca domestica), have sporadically been described as possible mechanical vectors of agents of nosocomial infections because they may carry human pathogens and also due to their ubiquity including in the hospital environments [1][2][3][4] .…”
mentioning
confidence: 99%
“…We observed that flying insects were present in all rooms of the pediatric ward selected for sampling insects and also inside the neonatal-ICU. Likewise, other studies conducted in different countries have demonstrated that dipteran insects can be found inside hospitals [1][2][3][4] . Smarova et al 7 found several other synanthropic arthropods inside several wards of a hospital but the most frequent were cockroaches and dipterans.…”
mentioning
confidence: 99%